2023
DOI: 10.1128/spectrum.00849-23
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Zebrafish with Diabetes and Alzheimer's Disease Treated with Pasteurized Akkermansia muciniphila

Abstract: The interaction between intestinal microflora and host affects the progression of diabetes and Alzheimer's disease. As a recognized next-generation probiotic, Akkermansia muciniphila has been shown to play a key role in the progression of diabetes and Alzheimer's disease, but whether A. muciniphila can improve diabetes complicated with Alzheimer's disease and its potential mechanism are unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…This is similar to a recent study that reported that the Icariin intervention significantly improved cognitive dysfunction in AD mice by elevating the abundance of Akkermansia and reducing the abundance of Mucispirillum. As a recognized next-generation probiotic, Akkermansia is closely related to the positive systemic effects on host metabolism and homeostatic immunity and significantly contributes to the progression of AD. , Akkermansia has been found to enhance the reduction of Aβ40–42 and ameliorate intestinal barrier dysfunction . Previous studies have suggested that Clostridium butyricum regulates gut homeostasis and induces IL-10-producing macrophages and response in anti-inflammatory; thus, it is a breakthrough in probiotics …”
Section: Discussionmentioning
confidence: 99%
“…This is similar to a recent study that reported that the Icariin intervention significantly improved cognitive dysfunction in AD mice by elevating the abundance of Akkermansia and reducing the abundance of Mucispirillum. As a recognized next-generation probiotic, Akkermansia is closely related to the positive systemic effects on host metabolism and homeostatic immunity and significantly contributes to the progression of AD. , Akkermansia has been found to enhance the reduction of Aβ40–42 and ameliorate intestinal barrier dysfunction . Previous studies have suggested that Clostridium butyricum regulates gut homeostasis and induces IL-10-producing macrophages and response in anti-inflammatory; thus, it is a breakthrough in probiotics …”
Section: Discussionmentioning
confidence: 99%
“…Akkermansia muciniphila ( A. muciniphila ) exhibited comparable functionalities, as evidenced by its significant amelioration of Aβ protein deposition and intestinal barrier dysfunction in the brains of APP/PS1 mice, and neurobehavioral assessments demonstrated notable enhancements in memory function and mitigation of obesity induced by a high-fat diet [ 108 , 109 ]. Subsequent investigations unveiled that pasteurized A. muciniphila yielded significantly superior outcomes in memory, anxiety, aggression, and social preference compared to untreated A. muciniphila [ 110 ]. By modulating gut microbiota, the authors also discovered that pasteurized A. muciniphila enhanced systemic metabolism and A protein deposition in the brain [ 110 ].…”
Section: Treatment Strategy Of Ad Based On Gut Microbiotamentioning
confidence: 99%
“…Subsequent investigations unveiled that pasteurized A. muciniphila yielded significantly superior outcomes in memory, anxiety, aggression, and social preference compared to untreated A. muciniphila [ 110 ]. By modulating gut microbiota, the authors also discovered that pasteurized A. muciniphila enhanced systemic metabolism and A protein deposition in the brain [ 110 ]. SLAB51 exhibited comparable efficacy to A. muciniphila in reducing blood glucose and lipids.…”
Section: Treatment Strategy Of Ad Based On Gut Microbiotamentioning
confidence: 99%
“…AD is primarily characterized by a progressive decline in memory and cognitive functions, leading to a diminished capacity for daily activities[ 13 ]. Pathologically, AD is marked by the deposition of amyloid plaques in neurons and the formation of neurofibrillary tangles, both contributing to altered brain tissue structure and function[ 14 - 16 ]. Currently, AD diagnosis predominantly relies on clinical assessments and neuroimaging, but these methods have limitations, particularly in early detection and disease progression monitoring[ 1 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, AD diagnosis predominantly relies on clinical assessments and neuroimaging, but these methods have limitations, particularly in early detection and disease progression monitoring[ 1 , 17 , 18 ]. Increasing evidence suggests that AD pathogenesis involves various factors, including neuroinflammation, immune dysregulation, and vascular dysfunction[ 14 ]. Consequently, identifying relevant biomarkers has become a crucial research focus.…”
Section: Introductionmentioning
confidence: 99%